2005
DOI: 10.1111/j.1442-9993.2005.01533.x
|View full text |Cite
|
Sign up to set email alerts
|

Raptorial birds and environmental gradients in the southern Neotropics: A test of species‐richness hypotheses

Abstract: We investigated the spatial patterns of raptor species richness in the southern Neotropics and tested three hypotheses that were most likely to explain spatial variations: ambient energy, productivity and habitat heterogeneity. We used non-linear regression analysis and eliminated alternative hypotheses by finding the best single environmental predictor of raptor species richness among potential evapotranspiration (PET), actual evapotranspiration (AET), mean annual temperature and precipitation and vegetation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Thus in Ctenomys, body size might be an important factor in avoiding predation by raptors. Since biodiversity increases as latitude decreases (Hillebrand, 2004), and this has been shown recently for southern Neotropical raptor species (Bellocq & Gó mez-Insausti, 2005), it is reasonable to assume that predators will be more abundant at lower latitudes, thus constituting a selective pressure on body size of tuco-tucos. However, as noted above, selectivity of prey by raptors may be influenced not only by prey size, but by prey activities and habitat and by predator energy requirements.…”
Section: Tablementioning
confidence: 99%
“…Thus in Ctenomys, body size might be an important factor in avoiding predation by raptors. Since biodiversity increases as latitude decreases (Hillebrand, 2004), and this has been shown recently for southern Neotropical raptor species (Bellocq & Gó mez-Insausti, 2005), it is reasonable to assume that predators will be more abundant at lower latitudes, thus constituting a selective pressure on body size of tuco-tucos. However, as noted above, selectivity of prey by raptors may be influenced not only by prey size, but by prey activities and habitat and by predator energy requirements.…”
Section: Tablementioning
confidence: 99%
“…The existence of mechanisms linking plant diversity to herbivore and higher trophic level diversity means that these may also be correlated with factors that drive plant diversity. Thus many studies have shown that animal diversity is frequently correlated with PET, actual evapotranspiration or remotely sensed measures of plant production such as the normalized difference vegetation index (NDVI; Currie 1991;Hawkins et al 2003;Bailey et al 2004;Seto et al 2004;Bellocq & Gó mez-Insausti 2005;Pautasso & Gaston 2005). Although the availability of water may affect the ability of animals to exploit their food resources, these correlations are generally indirect, mediated through the effects of water availability and temperature on plant diversity.…”
Section: (B) Chemical Energymentioning
confidence: 99%
“…Besides disturbance to habitat structure, diurnal raptors are also affected by hunting (Thiollay 1985(Thiollay , 1993, decreasing prey density (Jaksic et al 1992), environmental contamination (Hickey 1969) and trash consumption (Ellis and Lish 1999). Diurnal raptors may also show strong habitat selection, as studied by Robinson (1994) in Amazonian Peru, and by Julien and Thiollay (1996) in French Guyana, or respond to environmental gradients (Bellocq and Gó mez-Insausti 2005).…”
Section: Introductionmentioning
confidence: 99%